2017
DOI: 10.1590/1678-4162-8994
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal activity of leaves of Morus nigra against the cattle tick Rhipicephalus microplus

Abstract: The acaricidal activity of crude ethanolic extract and fractions from the leaves of Morus nigra (Moraceae) was carried out on female cattle ticks Rhipicephalus microplus, using the adult immersion test. The mortality and fertility of females exposed to different concentrations of hexane, chloroform and ethyl acetate fractions, as well as ethanolic extract of M. nigra with concentrations of 5, 10 and 25mg/ml were evaluated using three treatment groups, two control groups and triplicate tests. The study also ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…Table 2 shows the last products used at the farms studied, with most acaricide formulations containing organophosphate and pyrethroids. Such results corroborate with Silva (2010) and Dantas et al (2017), who reported that these two compounds are often used in combination because the action of pyrethroids is enhanced when associated with organophosphates. Among the six formulations tested, 50% presented average effectiveness in in vitro tests higher than 95% at all farms (Table 3).…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Table 2 shows the last products used at the farms studied, with most acaricide formulations containing organophosphate and pyrethroids. Such results corroborate with Silva (2010) and Dantas et al (2017), who reported that these two compounds are often used in combination because the action of pyrethroids is enhanced when associated with organophosphates. Among the six formulations tested, 50% presented average effectiveness in in vitro tests higher than 95% at all farms (Table 3).…”
Section: Resultssupporting
confidence: 91%
“…The associated formulations expressed better effectiveness indices (Table 3). Such results are similar to those obtained by Koler et al (2009), Abbas et al (2014), Higa et al (2016), Dantas et al (2017) and Silveira Neto et al (2017), who obtained more effective combinations in their studies due to the fact that associated products reacted together with different action mechanisms, allowing different tick repellent compounds to interact.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Esse estudo pode ser útil para o desenvolvimento de métodos alternativos de controle, pois destaca a interdependência entre os carrapatos e seus endossimbiontes(GUIZZO et al, 2017).Já o autor Showler et al (2020) utilizaram o Amblyomma americanum para avaliar a eficácia de um produto à base de terra de diatomáceas, uma substância natural que pode ser armazenada indefinidamente e que pode ainda fornecer proteção profilática aos bovinos contra ixodídeos. Em contrapartida,Pereira et al (2017) realizaram uma investigação química da polpa de frutos de Crescentia cujete L. na qual mostraram que a fase acetato de etila do extrato etanólico da polpa é um potencial controle alternativo para R. microplus e sua atividade está em parte associada ao seu principal composto, o ácido cinâmico Dantas et al (2017). constataram que a presença de compostos fenólicos, possivelmente relacionados com a atividade biológica demonstrada pelos extratos etanólicos bruto e das frações das folhas de Morus nigra (Moraceae), podem ser utilizados como auxiliares no controle contra o carrapato adulto de R. microplus.…”
unclassified